2021
DOI: 10.3390/app112311274
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aggregate Size on Recycled Aggregate Concrete under Equivalent Mortar Volume Mix Design

Abstract: In this paper, the effect of the original aggregate size of the recycled aggregate on the mechanical properties of the recycled aggregate concrete was evaluated. A series of concretes were produced in which natural aggregates, recycled aggregates, and original aggregates in recycled aggregates were matched for a single particle size distribution curve. The replacement levels of recycled aggregate were 25% and 50%, and equivalent mortar volume mix design was applied for recycled aggregate concrete. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…On the other hand, for RFA, the results of previous studies have reported that fine aggregate in the SSD state was more favorable to the mechanical strength of concrete than in the air-dry and oven-dry state [ 36 , 37 ]. Therefore, NCA, NFA, and RFA were used in the SSD state, and partially saturated RCA dried at room temperature 24 h before mixing after complete saturation was used [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, for RFA, the results of previous studies have reported that fine aggregate in the SSD state was more favorable to the mechanical strength of concrete than in the air-dry and oven-dry state [ 36 , 37 ]. Therefore, NCA, NFA, and RFA were used in the SSD state, and partially saturated RCA dried at room temperature 24 h before mixing after complete saturation was used [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…As the adhesive mortar content of RCA increased with the number of recycling cycles, the amount of cement, sand, and water required for unit concrete decreased in the order of R1, R2, and R3. A detailed description of the mix proportions of concrete designed with the EMV method can be found in our previous studies [ 23 , 24 ].…”
Section: Experimental Programmentioning
confidence: 99%
“…This intricate relationship underscores the importance of understanding Agronomy 2024, 14, 899 2 of 18 the structural attributes of soil aggregates, as they profoundly influence the stability of SOC. One pivotal metric utilized for assessing this stability is the mean weight diameter (MWD) [5]. A higher MWD value signifies enhanced aggregate stability, reflecting the effectiveness of soil aggregation in storing and preserving SOC.…”
Section: Introductionmentioning
confidence: 99%